Comparative study on early growth performance of dodonaea viscosa and leucaena leucocephala planted on different soil types applied on mine tailings dump at Renco Mine - Kaphaizi, Davison (Midlands State University, 2020)
Renco Mine tailings dump was commissioned in 1998, since 2006, a few tolerant plant species, most often exotics, with lower growth rates and not acclimatized to local conditions were once planted on the tailings dump using natural soil in an attempt to reclaim it. The main objective of the study was to compare early growth performance of Dodonaea viscosa and Leucaena leucocephala planted on biosolids (treatment) and natural soil (control) applied on an operational mine tailings dump at Renco Mine, Zimbabwe. Soil fertility analysis results shown that, both soils were very acidic, high in N and had traces of Ca, Mg and K. However, only boisoilds were high in P. Two rows with 125 planting holes each and an inter-row spacing of 2m were established on grass covered block area, and similarly on bare ground block area, and half of the holes randomly applied with either of the soil types in each block. A total of 250 Dodonaea viscosa species and 250 Leucaena leucocephala species were randomly planted on these planting stations in December 2017. Generally, Dodonaea viscosa planted on biosolids on grass covered area exhibited the highest overall monthly growth height increment interval of 3.1± 1.45cm. Similarly, Leucaena leucocephala recorded an overall monthly mean height growth increment interval of 2.27 ± 1.11cm. The highest monthly average Root Collar Diameter intervals were 0.03 ± 0.02cm on both species planted on biosolids with grass cover. Dodonaea viscosa planted on biosolids soil treatment on grass covered ground recorded the highest survival rate of 66.7%. Leucaena leucocephala planted on biosolids soil treatment on grass covered ground recorded its highest survival rate of 61.1%. Lowest survival rates were recorded on Leucaena leucocephala planted on natural soil on both bare ground and grass covered with survival rates of 22.2% and 33.3% respectively. Significant differences were observed in early growth performance of Dodonaea viscosa and Leucaena leucocephala on mine tailings dump (P<0.05). Similarly, significant differences were observed in early growth performance of species on different soil treatments applied on mine tailings dump (P<0.05) as well as early growth performance of species on grass covered soil and bare soil on mine tailings dump (P<0.05). Findings of the study indicate that, Dodonaea viscosa can be extensively used in revegetation of mine dumps, while Leucaena leucocephala can be relatively used with ameliorative measures on pH.